Accuracy of screening for gastric cancer using serum pepsinogen concentrations. Issue 5 (1st May 1999) - Kitahara, F; Kobayashi, K; Sato, T; Kojima, Y; Araki, T; Fujino, M A
Abstract : BACKGROUND/AIMS: The characteristics of pepsinogen screening for gastric cancer were investigated to establish a suitable cut off point for identifying gastric cancer, using endoscopic diagnosis as the yardstick. SUBJECTS/METHODS: Serum pepsinogen concentrations were measured in 5113 subjects who were also screened for gastric cancer by endoscopy. The cut off point for pepsinogen was determined using receiver operator characteristics curves. RESULTS: The most suitable cut off point was a pepsinogen I concentration of less than 70 ng/ml and a ratio of pepsinogen I to pepsinogen II of less than 3.0. Using this cut off point, the sensitivity and specificity of pepsinogen screening for gastric cancer were 84.6% and 73.5% respectively. All cases of gastric cancer in patients with severe atrophic gastritis were detected. However, two of four cases of gastric cancer in patients with mild atrophic gastritis were overlooked. In subjects with mild atrophic gastritis, when gastric cancer arises within the fundic gland region, the size of the lesion determines whether it is possible to detect cancer by serum pepsinogen screening. CONCLUSION: Pepsinogen screening has many advantages, including its suitability for combination with other screening methods because it is simple and inexpensive.